THE CRIMINALIZATION OF THE QUR'AN PERSPECTIVE AND IT'S CONTEXTUALIZATION IN INDONESIA - Marhaban, Nawawi (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
The Qur'an as the main source of law in Islam rules various kinds of criminal offenses and their punishments called JarÄ«mah. This is relevant to the purpose of God's laws implemented for the benefit and happiness of human beings. This article aims to present the discourse of Islamic criminal law in the Indonesian context. By using library research and content analysis as the analytical knife, this study found that the punishment in terms of the existence of texts in the Qur'an and hadith consists of two kinds. First, the punishments directly mentioned in the text are á¸¥udÅ«d, qiá¹£aá¹£, diyÄt and kafarÄt. Second, the punishment uncovered by the text is the ta'zÄ«r punishment. Furthermore, there are four kinds of relations in the punishment, namely; 1) principal punishment, 2) substitute punishment, 3) additional punishment, and 4) complementary punishment. In this study, there are also ten acts that are able to be criminalized with threats of á¸¥add and qiá¹£aá¹£ punishment, namely zinÄ, qaÅ¼f (accusing zinÄ without evidence), á¸¥irÄbah (robbery), sariqah (theft), syurb al-khamr (drinking wine), maisir (gambling), riddah (apostasy), murder, persecution, and al-bugyu (rebellion).